2022
DOI: 10.1099/ijsem.0.005596
|View full text |Cite
|
Sign up to set email alerts
|

Granulimonas faecalis gen. nov., sp. nov., and Leptogranulimonas caecicola gen. nov., sp. nov., novel lactate-producing Atopobiaceae bacteria isolated from mouse intestines, and an emended description of the family Atopobiaceae

Abstract: Two strictly anaerobic, Gram-stain-positive, non-motile bacteria (strains OPF53T and TOC12T) were isolated from mouse intestines. Strains OPF53T and TOC12T grew at pH 5.5–9.0 and 5.0–9.0, respectively, and at temperatures of 30–45 °C. The cell morphologies of these strains were short rods and rods, respectively, and the cells possessed intracellular granules. The major cellular fatty acids of OPF53T were C18  :  1 cis 9 and C18  :  1 cis 9 dimethyl acetal, whereas those of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The results showed that the most closely related strain was ‘ Olsenella congonensis ’ (YH-ols2216, 92.6 %; YH-ols2217 T , 92.7 %), which was below the defined threshold for delineation of bacterial genus [23]. However, ‘ O. congonensis ’ Marseille-P3359 T was not validly published, thus, the type strain within the following type species of closely related genera were used as reference strains: Granulimonas faecalis KCTC 25474 T [7], Leptogranulimonas caecicola KCTC 25472 T [7], Paratractidigestivibacter faecalis KCTC 15699 T , Parafannyhessea umbonata KCTC 22620 T , Thermophilibacter provencensis DSM 107455 T , Tractidigestivibacter scatoligenes DSM 28304 T , Olsenella uli KCTC 5039 T , Collinsella aerofaciens JCM 10188 T [24], Coriobacterium glomerans JCM 10262 T [3], and Enorma massiliensis DSM 25476 T [25]. The similarities between isolates YH-ols2216 and YH-ols2217 T and the type species of the most closely related genus Granulimonas ( G. faecalis KCTC 25474 T ) were 92.0 and 92.5 %, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results showed that the most closely related strain was ‘ Olsenella congonensis ’ (YH-ols2216, 92.6 %; YH-ols2217 T , 92.7 %), which was below the defined threshold for delineation of bacterial genus [23]. However, ‘ O. congonensis ’ Marseille-P3359 T was not validly published, thus, the type strain within the following type species of closely related genera were used as reference strains: Granulimonas faecalis KCTC 25474 T [7], Leptogranulimonas caecicola KCTC 25472 T [7], Paratractidigestivibacter faecalis KCTC 15699 T , Parafannyhessea umbonata KCTC 22620 T , Thermophilibacter provencensis DSM 107455 T , Tractidigestivibacter scatoligenes DSM 28304 T , Olsenella uli KCTC 5039 T , Collinsella aerofaciens JCM 10188 T [24], Coriobacterium glomerans JCM 10262 T [3], and Enorma massiliensis DSM 25476 T [25]. The similarities between isolates YH-ols2216 and YH-ols2217 T and the type species of the most closely related genus Granulimonas ( G. faecalis KCTC 25474 T ) were 92.0 and 92.5 %, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…C 18 : 1 ω 6 c was only detected as the dominant whole-cell fatty acid in isolate YH-ols2216. The dominant cellular fatty acid C 18 : 1 ω 9 c , while at different percentages, was also present in G. faecalis KCTC 25474 T [7], L. caecicola KCTC 25472 T [7], O. uli KCTC 5039 T , Prf. umbonata KCTC 22620 T , Tr.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations